The Stereotype Content Model as an Explanation of Biased Perceptions in a Medical Interaction: Implications for Patient-Provider Relationship - Jain, Parul (Health communication, 2022)
This experimental investigation uses the stereotype content model (SCM) to explain the biases associated with the perceptions of healthcare providers and the subsequent impact of such biased perceptions. Specifically, the 2 (gender: male, female) by 2 (race: Arab, Caucasian) between-subjects experiment examined the impact of physician race and gender on people's perceptions regarding physician's communication competence, trust, and intentions to visit. The findings indicate that female physicians are considered not only warmer but also more competent than male physicians. White physicians are considered less competent overall than their minority counterparts, though no differences in perceived patient-centered communication behaviors were observed. In addition, perceived competence and warmth mediated the effect of physician gender and race (only warmth) on the perceptions of trust, physician's use of patient-centered communication, and intentions to visit. The theoretical and practical implications of the study are discussed.